PENINGKATAN PRESTASI BELAJAR MEMBACA DAN MENULIS MELALUI ALAT PERAGA - Sri Purwati (LPPM UNISDA, 2019)
This study aims to improve the achievement of learning to read and write through the use of teaching aids. This research is classified as action research with steps: planning, implementing procedures, reflection. The subjects of this study were Class I students at Palangan II Elementary School, Karangbinangun Subdistrict, Lamongan. The results of the analysis and reflection conducted by colleagues show that the interest of students in class I (one) in learning to read and write words, simple sentences with reasonable pronunciation and intonation has increased, in the initial condition 26.66% to 40.00% in cycle I means up 13.34%. The results of students in the final test or on a daily tests increased presentase students completed study on the initial conditions of 46% to 60% in the first cycle means an increase of 14% and to 87% in the second cycle rose 27%. Indicators of success about student learning outcomes in this study are determined at least 75% of the number of students who have reached KKM means that they have succeeded.